Physicochemical characteristics and pyrolysis kinetics of raw and torrefied hybrid poplar wood (NM6 – Populus nigra). Issue 3 (2nd April 2020) - Regmi, Bharat; Dutta, Animesh; Pradhan, Ranjan R.; Arku, Precious
ABSTRACT: The present research work is an attempt to focus on thermal kinetics of raw and torrefied hybrid poplar wood ( Populus nigra – NM6). The results of the experiment under the optimal condition based on mass and energy yield, which was found to be 270 °C, were evaluated for physiochemical and kinetic characteristics. Comparative pyrolysis of raw and torrified hybrid poplar wood was carried out to understand the enhancement of biofuel characteristics and kinetics after torrefaction. Torrefaction of hybrid poplar led to decreased O/C and H/C ratios due to removal of low-quality volatile materials from thermal degradation of hemicelluolose, resulting in increased higher heating value. The kinetic parameters were determined by different modelling approaches. The model free pyrolysis kinetics approach was found to be the best applicable model. Results of the Kissinger-Akahira-Sunose (KAS) and Ozawa-Flynn-Wall (OFW) methods indicate that torrefied hybrid poplar has a decreased activation energy of 168 kJ/mol and 170 kJ/mol compared to raw poplar's 202 kJ/mol and 201 kJ/mol, respectively. Fourier transform infrared (FTIR) analysis indicates that torrefied hybrid poplar became more hydrophobic, compared with raw poplar, due to increased aromaticity.